Do high speed rail configurations matter to tourist arrivals? Empirical evidence from China's prefecture-level cities. (December 2021) - Deng, Taotao; Gan, Chen; Du, Huiping; Hu, Yukun; Wang, Dandan
Abstract: Based on data of 286 Chinese cities from 2006 to 2015, the paper applies Difference-in-Difference (DID) model to investigate whether and how High-Speed Railway (HSR) influences the tourist arrivals. Empirical results suggest that 1) although HSR opening can significantly promote tourist arrivals, the multi-stage DID model indicates a time-lag effect of HSR on tourism. 2) The positive effects of HSR opening on tourist arrivals increase gradually. 3) Improving HSR frequency helps cities to attract more tourists. 4) The location of HSR station has no significant impact on tourist arrivals. 5) Compared with the ordinary station, the hub station of HSR in the city can attract more tourist arrivals through an enhanced network effect.